Pengaruh Gerak U-Turn pada Bukaan Median terhadap Karakteristik Arus Lalu Lintas - sri anggreni; Firmanilah Kamil; Julyan Purnomo (Journal of Research and Inovation in Civil Engineering as Applied Science, 2022)
Transportation problems in big cities in Indonesia, especially on Jalan R. Suprapto, Ketapang Regency are increasing from time to time in line with population growth, rapid growth in the number of vehicles and vehicle ownership, urbanization and an inefficient public transportation system. This has an impact on the decrease in the performance level of the road segment, including the U-Turn motion behavior at the road median opening. This study aims to determine traffic characteristics, road capacity, road service level (LOS), the average time for vehicles to perform U-turns, queue lengths and alternatives that will be applied in this study based on the 1997 MKJI guidelines. From the results of research and discussion on Jalan R. Suprapto the characteristic value of traffic flow which consists of traffic volume at rush hour from the direction of Jl. R. Suprapto – Jl. Gatot Subroto at 513.8 smp/hour and for the direction of Jl. Gatot Subroto – Jl. R. Suprapto at 651.35 smp/hour. The vehicle speed is 49.86 km/hour. Traffic density for the direction of Jl. R. Suprapto – Jl. Gatot Subroto of 10.24 smp/km and for the direction of Jl. Gatot Subroto – Jl. R. Suprapto 13.1 pcu/km. The road segment capacity is 5,422.3 pcu/hour. The value of the road service level obtained an A value.